Picking battles: correctional officers, rules, and discretion in prison - Haggerty, Kevin D. (Criminology, 2021)
To outsiders, prisons vacillate between visions of regimented order and anarchic disorder. The place of rules in prison sits at the fulcrum between these two visions of regulation. Based on 131 qualitative interviews with correctional officers across four different prisons in western Canada, we examine how correctional officers understand and exercise discretion in prison. Our findings highlight how an officer's habitus shapes individual instances of discretionary decision-making. We show how officers modify how they exercise discretion in light of their views on how incarcerated people, fellow officers, and supervisors will interpret their decisions. Although existing research often sees a correlation between “rule-following” by incarcerated individuals and official statistics on such misdeeds, our data highlight that official statistics on rule violations do not easily represent the rate or frequency of such misbehavior. Instead, these numbers are highly discretionary organizational accomplishments. Our findings advance an appreciation for correctional officer discretion by focusing on the range of factors officers might contemplate in forward-looking decisions about applying a rule and how they rationalize the nonenforcement of rules.